Pilot Study of Linking Web-Based Supplemental Interpretive Information to Laboratory Test Reports. Issue 6 (August 2015) - Shirts, Brian H.; Gundlapalli, Adi V.; Jackson, Brian
Abstract : Electronic medical records have the ability to link to reference material, providing clinicians with immediate access to information relevant to patient care. Adding relevant links to laboratory test results could add value while minimizing the volume of ancillary text presented. We provided Web-based universal resource locator (URL) links with all results of 7 laboratory tests ordered at ARUP Laboratories (Salt Lake City, UT). URL links provided were modified 7 months later, and use between initial and subsequent URLs was tracked to establish frequency and duration of access to supplemental Web information. Monthly Web-site hit rates for individual tests varied from 0.00% to 3.00% (median, 0.12%). Rare and specialty tests averaged higher hit rates. There was no decay in hit rate 9 months after URLs were removed from test reports. We conclude that links to reference material are accessed by clinicians. The use of Web links months after links were no longer published raises an important issue of long-term maintenance and the resources required to support these features.